Securing Development : Public Finance and the Security Sector - Harborne, Bernard; Dorotinsky, William; Bisca, Paul M. (Washington, DC: World Bank, 2016)
This book highlights the role played by public finance in the delivery of security and criminal justice services. It seeks to strengthen policy and operational dialogue on security sector issues by providing national and international stakeholders with key information on security expenditure policy and management.